On the connection between creativity and aesthetics - Brown, Steven (Frontiers in Psychology, 2024)
Within cognitive psychology, there are separate experimental fields devoted to the study of creativity, on the one hand, and aesthetics, on the other, with virtually no cross-talk between them. In this article, I propose a means of uniting creativity and aesthetics via a consideration of the mechanisms of cultural evolution. I call this the creativity/aesthetics cycle. The basic tenet of the model is that creativity and aesthetics mediate, respectively, the processes of variation (production) and selection (perception or consumption) in evolutionary models of culture. By means of this cycle, creators produce works that they hope will be evaluated positively by consumers, where such appraisals ultimately feed back to influence the subsequent decision-making processes of creators. I discuss the implications of this model for the fields of creativity and aesthetics.